2018
DOI: 10.1590/1678-4685-gmb-2017-0175
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic variability of iris color in Buenos Aires population

Abstract: The aim of this work was to describe the phenotypic and genotypic variability related to iris color for the population of Buenos Aires province (Argentina), and to assess the usefulness of current methods of analysis for this country. We studied five Single Nucleotide Polymorphisms (SNPs) included in the IrisPlex kit, in 118 individuals, and we quantified eye color with Digital Iris Analysis Tool. The markers fit Hardy-Weinberg equilibrium for the whole sample, but not for rs12913832 within the group of brown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 55 publications
0
13
0
4
Order By: Relevance
“…In our study, no association may have been found by the low frequency of the allele A in our sample. Hohl et al in studies conducted in Buenos Aires population also found no significants associations between rs1393350 and eye color, he comments that the genetic context of iris color in Argentina is different from other countries due to population miscegenation (Hohl, Bezus, Ratowiecki, & Catanesi, 2018), as is the case in Brazil, according to Hohl, markers already elucidated in European countries should be carefully applied to populations with different characteristics.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, no association may have been found by the low frequency of the allele A in our sample. Hohl et al in studies conducted in Buenos Aires population also found no significants associations between rs1393350 and eye color, he comments that the genetic context of iris color in Argentina is different from other countries due to population miscegenation (Hohl, Bezus, Ratowiecki, & Catanesi, 2018), as is the case in Brazil, according to Hohl, markers already elucidated in European countries should be carefully applied to populations with different characteristics.…”
Section: Discussionmentioning
confidence: 97%
“…which are more frequent in these groups [60][61][62][63]64,65 . Future research that addresses these shortcomings will not only advance the field of forensics but also will facilitate geneticallyinformed studies such as this one in admixed populations.…”
Section: Limitationsmentioning
confidence: 99%
“…Recently, genetic variants associated with pigmentation traits have been discovered in populations of other ancestries 59 . Although a similar predictive algorithm is not available for them yet, HIrisPlex-S (or its related versions: HIrisPlex and IrisPlex) has been tested in some Latin American and Asian populations, showing an acceptable performance for eye and hair colour predictions, better than for skin pigmentation, but exhibiting limitations in the prediction of intermediate phenotypes, which are more frequent in these groups 60–63, 64, 65 . Future research that addresses these shortcomings will not only advance the field of forensics but also will facilitate genetically- informed studies such as this one in admixed populations.…”
Section: Limitationsmentioning
confidence: 99%
“…In addition, the whole corneal region image was selected for image analysis in previous studies. However, the iris itself has color and texture features and has demonstrated individual differences [24,25]. Therefore, we segmented corneal pupil region images for analysis to ensure the accuracy and reliability of the measured data.…”
Section: Digital Analysis Of Postmortem Corneal Imagesmentioning
confidence: 99%